ANALISIS KONDISI SOSIAL EKONOMI MASYARAKAT SEKITAR TAMAN NASIONAL GANDANG DEWATA - Sarif, Muhammad; Demma semu, Yulsan; Medi (Universitas Nusa Bangsa, 2023)
Gandang Dewata National Park was designated as a conservation area because it has biodiversity and a unique ecosystem. Ecosystem types in this area are based on altitude or topographic conditions, namely Lowland Forest, Lower Mountain Forest, Upper Mountain Forest and Sub-Alpine Forest. This research aims to obtain an explanation of the socio-economic problems of the community around the Gandang Dewata National Park (TNGD), the level of community dependence on the National Park area and the contribution of income from the park to the total income of farmers. The research was carried out in Mamasa Regency in the TNGD Area, West Sulawesi Province. The method used in this research is interviews. Respondents in this study were chosen randomly. Data was analyzed descriptively qualitatively and quantitatively. The results of this research show that basic data and information regarding the socio-economic conditions of the people of Taupe Village, one of the TNGD buffer villages, shows that out of the 84 respondents interviewed, the socio-economic conditions of the people of Taupe Village work as farmers. 90% of this is because the village's irrigation conditions are still in good condition. The community is dependent on the area, namely 56% know the village boundaries and the location where the community lives is outside the area. Apart from that, the community's dependence on forests consists of rice fields and gardens. Utilization of forest products in the form of firewood, honey, aloes, bamboo, rattan and game products. Commodities based on agricultural, livestock, plantation and forestry products are coffee, cloves, cinnamon, patchouli, honey, cassava pork, aloes and broiler chicken. Most people (77%) do not know about TNGD